2013
DOI: 10.1093/bioinformatics/btt470
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factor binding sites from ChIP-seq data at high resolution

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…Chromatin states were predicted across the genome using ChromHMM (Ernst and Kellis 2012). p300 peaks were detected using the peakzilla software (Bardet et al 2013). See Supplemental Methods for details.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin states were predicted across the genome using ChromHMM (Ernst and Kellis 2012). p300 peaks were detected using the peakzilla software (Bardet et al 2013). See Supplemental Methods for details.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some ChIP-seq peak-callers do not account for strand-specific information, while others just compute strand cross-correlation to estimate the fragment length, afterwards shifting the reads with respect to the other strand (Bailey et al, 2013). Software tools like GeneTrack (Albert et al, 2008), GPS-GEM (Guo et al, 2012), peakzilla (Bardet et al, 2013) and MACS (Feng et al, 2012) have been used for peak-calling in ChIP-exo data-sets. However, GeneTrack was designed with ChIP-chip and ChIP-seq in mind, thus requiring manual matching of ChIP-exo peakpairs located nearby on opposed DNA strands (Rhee and Pugh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Choice of peak calling algorithm and parameters were based on published similar work (Cohen et al, 2015;Han et al, 2013;Huggins et al, 2016;Li et al, 2011;Sebe-Pedros et al, 2016). AqATF4 peaks were also detected using the Peakzilla software (Bardet et al, 2013) relative to input DNA (-c 2 -s 3).…”
Section: Chip-seq Data Analysesmentioning
confidence: 99%
“…Another peak-caller, Peakzilla (Bardet et al, 2013), identified 814 peaks, 80% of which belonged to the MACS2 peak sets. Manual inspection of the read coverage tracks of the Peakzilla peaks that were not identified using MACS2 showed a relatively poor enrichment for AqATF4 in those regions and suggested that the peakzilla parameters chosen were not optimal.…”
Section: Aqatf4 Occupancy Is Not Promoter-proximalmentioning
confidence: 99%